Study on the Failure Mechanism of the Polymorphic Mixture for Remanifactured Machinery Parts - Liu, C.H.; Li, W.Y.; Rao, W.Z.; He, K. (Проблемы прочности, 2018)
The polymorphic mixture failure mode for multiple heterogeneity of remanifactured (RM) machinery parts makes it difficult to assess their lifetime. The Weibull distribution failure model of RM parts (substrate, coating layer, bonding surface and sudden failure) is constructed with failure time statistics of the parts in service, the latter is used to characterize the failure patterns of RM parts. In view of the multiple heterogeneity of RM parts, the Kaplan–Meier type decoupling method is used to analyze four sets of failure statistics, and each state of the Weibull failure function of the above parts is solved. It reveals the in-service failure mechanism of polymorphic mixtures for multiple heterogeneity of RM machinery parts. The validity and feasibility of the model are verified by the case study. Research results provide the theoretical basis for the design and preparation of a RM alloy powder and the improvement of RM technology. Moreover, the method for lifetime prediction and failure time evaluation of RM parts is proposed and validated Характер разрушения полиморфной смеси в условиях множественной гетерогенности модифицированных деталей затрудняет оценку срока службы оборудования. Модель разрушения распределения Вейбулла (разрушение подложки, наружного слоя, поверхости сцепления, мгновенное разрушение) построена на основании статистических данных о времени разрушения детелей в условиях эксплуатации. Использован метод разделения Каплана Мейера для анализа четырех множеств статистик разрушения, выполнено решение каждого состояния функции Вейбулла, что позволило установить механизм разрушения полиморфных смесей в условиях эксплуатации при множественной гетерогенности модифицированных деталей оборудования. На примере выполнения моделирования верифицированы достоверность и применимость модели. Создана теоретическая основа для разработки и изготовления порошка сплава и совершенствования технологии модифицирования. Разработан метод прогнозирования срока службы и оценки периода разрушения модифицированных деталей.